2017
DOI: 10.1016/j.ajog.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

The limits of electronic fetal heart rate monitoring in the prevention of neonatal metabolic acidemia

Abstract: Expert, algorithm-assisted fetal heart rate interpretation has the potential to improve standard clinical performance by facilitating significantly earlier recognition of some tracings that are associated with metabolic acidemia without increasing the rate of operative intervention. However, this improvement is modest. Of infants who are born with metabolic acidemia, only approximately one-half potentially could be identified and have delivery expedited even under ideal circumstances, which are probably not re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 23 publications
2
83
2
4
Order By: Relevance
“…The assessment of shortterm variations (STV) and long-term variations (LTV) was found to be of use in diagnosing fetal compromise. These variables used in CTG monitors are known as the most evident markers of fetal distress [4,9]. But the duration of the recording should be not less than 1 hour or, at least, 30 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The assessment of shortterm variations (STV) and long-term variations (LTV) was found to be of use in diagnosing fetal compromise. These variables used in CTG monitors are known as the most evident markers of fetal distress [4,9]. But the duration of the recording should be not less than 1 hour or, at least, 30 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…But the duration of the recording should be not less than 1 hour or, at least, 30 minutes. This time interval is known to be associated with better sleep/awake fetal status ratio [2,4]. Therefore, the application of the proposed fetal HRV variables will help to use fetal noninvasive ECG tracing of the only 10 minutes long.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These numbers are not that different from those from a similarly designed study that found that 46% of neonates with metabolic acidemia would have been delivered via operative delivery if a fetal heart rate monitoring algorithm was applied. 7 One response to a study like this is to point out the limitations of fetal heart rate monitoring -it is an imperfect tool. However, if fetal heart rate monitoring is used judiciously, there appears to be opportunity to improve outcomes.…”
Section: + Related Articlementioning
confidence: 99%
“…To date, this goal has been elusive. 9,10 The purpose of this study was to determine if the use of a standardized approach for labors complicated by Category II fetal heart rates with "significant decelerations" would improve neonatal outcome and determine the impact on the rate of primary cesarean and operative vaginal delivery birth rates.…”
mentioning
confidence: 99%